2020
DOI: 10.11591/ijere.v9i4.20692
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of students on the use of interactive online learning technologies in Mauritius

Abstract: <p>With the advent of e-learning, advocates use the term interactivity instead of interaction among students, and between the teacher and the students. Many universities use Moodle for online teaching and learning. This paper explores the perceptions and experiences of students in three Higher Education Institutions (HEIs) in Mauritius. A mixed-methods approach was used, with an online survey questionnaire administered to 600 students and focus group discussions were conducted with 15 students from these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 14 publications
(16 reference statements)
1
40
0
3
Order By: Relevance
“…While some elements of good teaching do cut across physical and virtual classrooms, online teaching also requires distinctive instructional strategies to promote engagement. Previous research carried out in Mauritius, where a majority of our participants were based, has identified a need for academics to move towards more social constructivist (knowledge construction through interaction with others)., connectivist (networking), and heutagogical (student-centred, self-determined) instructional approaches to promote student engagement (Ramkissoon et al 2020). Gilly Salmon's e-tivities mentioned earlier (Salmon 2013) provide an appropriate framework which academics can use to promote more active online learner participation through a scaffolded approach, whereby learners receive more initial support which is gradually relinquished as they take greater ownership of their learning.…”
Section: Discussionmentioning
confidence: 99%
“…While some elements of good teaching do cut across physical and virtual classrooms, online teaching also requires distinctive instructional strategies to promote engagement. Previous research carried out in Mauritius, where a majority of our participants were based, has identified a need for academics to move towards more social constructivist (knowledge construction through interaction with others)., connectivist (networking), and heutagogical (student-centred, self-determined) instructional approaches to promote student engagement (Ramkissoon et al 2020). Gilly Salmon's e-tivities mentioned earlier (Salmon 2013) provide an appropriate framework which academics can use to promote more active online learner participation through a scaffolded approach, whereby learners receive more initial support which is gradually relinquished as they take greater ownership of their learning.…”
Section: Discussionmentioning
confidence: 99%
“…Online learning showed a result of low motivation related to the low learning attitude in language learning (Ramkissoon et al, 2020;Satyawan et al, 2021). Losing motivation happens when students lose their time management skills because of the learning environment that does not let the learners learn in a conducive condition (Chepy et al, 2016;Suardana & Simarmata, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding of this study revealed that mostly the students frequently use Discussion forum, Messenger/twitter/Facebook/WhatsApp, Chat room, Video and Facetime/Skype/Zoom may due to their online learning experience in daily bases with their lectures. The reason of high percentage of students' preference might be well explained by [19] who discovered in their study that students preferred due to facility for knowledge sharing and construction, interactivity, usability, respect for privacy and instant communication.…”
Section: Fig 2: Frequency Of Communication Tool Used By the Studentsmentioning
confidence: 98%